'n Ondersoek na die fisiologiese en biochemiese profiel van fietsryers tydens ultralangafstand kompetisies - Barnard, Justhinus Gerhardus (University of the Free State, 1987)
During the Rapport Cycling Tour (~2 000 km), which is annually marked by hard sustained cycling, the elevated metabolic state of the human body results in heat production that is greateer than heat loss. This imbalance may be endured for long periods and weather conditions can pose particular problems such as dehydration, overheating and fluid replacements for cyclists. During one stage (~210 kom) we observed a 4.7% reduction in body mass. This degree of dehydration exceeded the safety levels of 3% found by Wyndham and Strydom (1969). An investigation was conducted to establish the physiological profile of the white South-African road cyclist, before, during and after different stages of the Rapport Tour, and to assess the influence of sustained physical exercise on the human metabolism under controlled conditions. To accomplish these objectives, anthropometrical, physiological and biochemical parameters were assessed in a number of highly conditioned road cyclists during 4 different Rapport Cycling Tours. The cyclists as a group were characterized by a 1,6; 4,9 and 2,97 somatotype with a mean percentage body fat amounting to 5,7%. The mean VO2-max was 71,4 ml/kg/min with a range of 66,3 - 82,5 ml/kg/min. Average heart rate during a simulated cycling stage varied between 121 beats per minute (downhill) to 179 beats per minute (sprint) with an average of 137 beats per minute on the open road with the individual cyclist at the front of the pace line. The average estimated oxygen cost amounted to 55% of the VO2-max. An number of heamatological parameters, including serum iron and serum ferritin, plasma electrolytes, parameters of hepatic and renal functions and plasma enzymes were measured, before the tour, after 7 stages and after the final stage. The study provides the following conclusions: a) There are relatively minor changes in blood parameters during the 14 day cycling, indicating that dietary supplementation of electrolytes is probably unnecessary. b) There is no evidence of iron-deficiency in the cyclists. c) The small rise in creatine kinase (CK) levels is remarkable, indicating that cycling has a different effect on muscle than does running. d) Although most cyclists maintained normal blood glucose levels during the race, isolated cases of hypoglycaemia were recorded and these responded rapidly to glucose ingestion. This indicates the need for a high carbohydrate diet for the 14 days during the race, and for glucose supplementation ad libitum. e) Although the water content of plasma diminishes during exercise yielding some degree of hemoconcentration, the negative effects of this can be reduced by increasing the fluid intake since the magnitude of this response is believed to be dependent upon fluid intake and ambient conditions. Since hemoconcentration in our study was not present in a sufficient degree to increase hematocrit (Hct), hemoglobin (Hb) or electrolyte concentrations significantly, we wish to suggest that the incrase in protein was related to the contribution of lymph rather than the loss of vascular water. f) All the creatinin clearances were normal and none of the cyclists developed hematuria. g) The fact that some cyclists tested positive during routine doping control was mainly due to the ignorence of the cyclists and their coaches since certain cough and cold remedies as well as tonics contain banned substances. We argued that this should never be accepted as an excuse. h) A low sodium and chloride syndrome seems to manifest itself 4 and 8 hours after the completion of a stage of the cycling tour. These findings indicate the need for additional studies.
Thesis (D.Phil. (Biokinetics))--University of the Free State, 1987
Keywords: Cycling; Rapport Cycling Tour; South-African road cyclist; Physical exercise